PENYELEKSIAN JURUSAN TERFAVORIT PADA SMK SIRAJUL FALAH DENGAN METODE SAW - Nurlela, Siti; Akmaludin, Akmaludin; Hadianti, Sri; Yusuf, Lestari (Jurnal Pilar Nusa Mandiri, 2019)
SMK Sirajul Falah is a Vocational High School located in the Bogor area. However, the selection of the favorite majors in SMK Sirajul Falah is still qualitative so that the process of choosing the favorite majors become not accurate. This is what makes the need for a method that is able to manage the data of the selection of the favorite majors and generate a ranking of the calculation of the weight of the selection of the favorite majors. In the selection of these favorite majors, there is a method of Simple Additive Weighting (SAW) which can be used in quantitative problem-solving. The SAW method is used to compare each criterion with one another, so as to give the results of the favorite majors and provide an assessment of each department at the Sirajul Falah Vocational School.